SOCIAL MEDIA MARKETING; STRATEGI KOMUNIKASI BISNIS ERA DIGITAL (Studi Analisis Portal TaniFund.com) - Mellyan Mellyan (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2020)
The digital world with all its novelty brings changes in every field. This was triggered by the advent of internet technology. Various sectors adapt to the emergence of the technology, one of the business. At the previous two decades, business world is still prevalent using traditional methods, now the business world uses digital media, including social media in it for promotion and business development. Tanifund is a financial funding platform that focuses on agriculture, animal husbandry, and fisheries. It is interesting to study Tanifund because there are big differences in the era of digital agriculture that